Hubungan Perilaku Dan Kualitas Fisik Rumah Dengan Kejadian Tbc Paru Di Wilayah Kerja Puskesmas Kediri 1 Tahun 2020 - AA Istri Ratih Dwi Pratiwi; I Wayan Sudiadnyana (Jurnal Kesehatan Lingkungan (JKL), 2021)
Abstract:. The increase in cases of pulmonary tuberculosis in a region is caused by physical quality factors of the house and behavioral factors. The purpose research was to determine the relationship between behavior and physical quality of the home with the incidence of pulmonary tuberculosis in the Kediri Community Health Center 1. The type of observational research was retrospective with a case control design. Case group samples were 40 tuberculosis patients at the Kediri Health Center 1 in 2018. Samples of the control group were 40 people who had never suffered from tuberculosis and had the characteristics of a case group. Data collection used questionnaire sheets for behavior and observation sheets for the physical quality of the house and  analyzed with chi square statistical test. Based on the results of the chi square test showed there is a relationship between behavior (p = 0,000 CC = 0,363) and physical quality of the house (p = 0,000 CC = 0,430) with the incidence of pulmonary tuberculosis. Suggestions that for the community to pay more attention to the health and cleanliness of the house